ETHAN FROME’S CHARACTER DEVELOPMENT IN WHARTON’S ETHAN FROME - Budiarto U Sugeha; Tini Mogea; Elizabeth Z Oroh (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The aim of this research is To find out Ethan’s character development portrayed through his characteristics in the novella.In this study, the writer employed qualitative research in which the data gathered in form of words and quotations. In analysing this novel, the writer applies objective approach because this analysis will be only focused on the literary work itself without looking at the external aspects of the literary work. It means that the writer only pay attention to the internal parts of the story in the novel. The result of this research shows that Ethan character development are influenced by people around him, in this case, Zeena and Mattie. He experience a view of changes of his character; hopeful into hopeless, responsible into irresponsible, faithfulness into unfaithful, and happiness into unhappiness.